Recognition and management of palatogingival groove: Hidden trap in the tooth-A case report - Bista, Soni; Ranjit, Rebicca; Subedi, Suraksha; Kunwar, Deepa (Journal of Gandaki Medical College-Nepal, 2022)
Palatogingival groove is a developmental anomaly, usually found on the palatal surface of maxillary incisor teeth. This hidden trap harbors plaque and bacteria around the tooth, ensuing periodontal destruction with or without pulpal pathologic changes. Several treatment modalities have been proposed for its management ranging from endodontic treatment, periodontal therapy or combined. Here, we present a case of a type II palatogingival groove causing endodontic- periodontal lesion successfully managed by endodontic treatment followed by periodontal surgery with an uneventful healing. Thus, this anomaly should be recognized early with timely intervention to avoid widespread involvement.